Changes in lipidomic profile by anti-retroviral treatment regimen: An ACTG 5257 ancillary study. Issue 30 (30th July 2021) - Chaudhary, Ninad S.; Kind, Tobias; Willig, Amanda L.; Saag, Michael S.; Shrestha, Sadeep; Funderburg, Nicholas; Wiener, Howard W.; Overton, E. Turner; Irvin, Marguerite R.
Abstract : Abstract: High cardiovascular disease risk in people living with HIV is partly attributed to antiretroviral therapy (ART). Lipid response to ART has been extensively studied, yet, little is known how small molecule lipids respond to Integrase inhibitor-based (INSTI-based) compared to Protease inhibitor-based (PI-based) ART regimens. Ancillary study to a phase 3, randomized, open-label trial [AIDS Clinical Trial Group A5257 Study] in treatment-naive HIV-infected patients randomized in a 1:1:1 ratio to receive ritonavir-boosted atazanavir (ATV/r), ritonavir-boosted darunavir (DRV/r) (both PI-based), or raltegravir with Tenofovir Disoproxil Fumarate-TDF plus emtricitabine (RAL, INSTI-based). We examined small molecule lipid response in a subcohort of 75 participants. Lipidomic assays of plasma samples collected pre- and post-ART treatment (48 weeks) were conducted using ultra-performance liquid chromatography coupled to time-of-flight mass spectrometry. The effect of ART regimens was regressed on lipid species response adjusting for the baseline covariates (lipids, age, sex, race, CD4 level, BMI, and smoking). Results were validated in the Centers for AIDS Research Network of Integrated Clinical Systems study (N = 16). Out of 417 annotated lipids, glycerophospholipids ( P = .007) and sphingolipids ( P = .028) had a higher response to ATV/r and DRV/r compared to RAL. The lysophosphatidylcholine (LPCs(16:1), (17:1), (20:3)) and phosphophatidylcholine species (PCs(40:7), (38:4)) had an opposite response to RAL versus ATV/r in the discovery and validation cohort. The INSTI-based regimen had an opposite response of ceramide species ((d38:1), (d42:2)), PCs((35:2), (38:4)), phosphatidylethanolamines (PEs(38:4), (38:6)), and sphingomyelin(SMd38:1) species compared with the PI-based regimens. There were no differences observed between 2 PI-based regimens. We observed differences in response of small molecule lipid species by ART regimens in treatment-naive people living with HIV. Abstract : Supplemental Digital Content is available in the text